2017
DOI: 10.1111/jnc.14054
|View full text |Cite
|
Sign up to set email alerts
|

Lesion of the basal forebrain cholinergic neurons attenuates sleepiness and adenosine after alcohol consumption

Abstract: Alcohol has a profound effect on sleep. However, neuronal substrates mediating sleep-promoting effects of alcohol are unknown. Since the basal forebrain (BF) cholinergic neurons are implicated in the homeostatic regulation of sleep, we hypothesized that the BF cholinergic neurons may have an important role in sleepiness observed after alcohol consumption. 192-IgG-saporin (bilateral BF infusions) was used to selectively lesion BF cholinergic neurons in adult male Sprague-Dawley rats. Standard surgical procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…For instance, in adult rodents, acute binge alcohol has been shown to have sleep disrupting effects (Sharma, Sahota, & Thakkar, 2014), associated with reductions in the expression of equilibrative nucleoside transporter 1 (ENT1) (Sharma, Gonda, & Tarazi, 2018). Chronic ethanol administration has also been shown to lead to sleep disruption in adult rodents (Irwin, Miller, Christian Gillin, Demodena, & Ehlers, 2000;Mukherjee, Kazerooni, & Simasko, 2008;Mukherjee & Simasko, 2009;Sanchez-Alavez, Benedict, Wills, & Ehlers, 2019;Sharma, Engemann, Sahota, & Thakkar, 2010;Veatch, 2006), and it has been suggested that both cholinergic and adenosinergic mechanisms in basal forebrain may in part be responsible for alcohol-induced sleep disruption in adults (Ehlers, Criado, Wills, Liu, & Crews, 2011;Sharma, Sahota, & Thakkar, 2017). However, few studies have investigated the mechanisms underlying the effects of adolescent alcohol exposure on sleep.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in adult rodents, acute binge alcohol has been shown to have sleep disrupting effects (Sharma, Sahota, & Thakkar, 2014), associated with reductions in the expression of equilibrative nucleoside transporter 1 (ENT1) (Sharma, Gonda, & Tarazi, 2018). Chronic ethanol administration has also been shown to lead to sleep disruption in adult rodents (Irwin, Miller, Christian Gillin, Demodena, & Ehlers, 2000;Mukherjee, Kazerooni, & Simasko, 2008;Mukherjee & Simasko, 2009;Sanchez-Alavez, Benedict, Wills, & Ehlers, 2019;Sharma, Engemann, Sahota, & Thakkar, 2010;Veatch, 2006), and it has been suggested that both cholinergic and adenosinergic mechanisms in basal forebrain may in part be responsible for alcohol-induced sleep disruption in adults (Ehlers, Criado, Wills, Liu, & Crews, 2011;Sharma, Sahota, & Thakkar, 2017). However, few studies have investigated the mechanisms underlying the effects of adolescent alcohol exposure on sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Vehicle (1% DMSO in ACSF; 50 nL/side) and/or melatonin (500 pmol/50 nL/side) microinjections were performed at the onset of active/dark period on subsequent days (counterbalanced). Microinjections were carried out as described previously . In brief, mouse was removed out of its cage, gently swaddled in a towel.…”
Section: Methodsmentioning
confidence: 99%
“…Microinjections were carried out as described previously. 58,61 In brief, mouse was removed out of its cage, gently swaddled in a towel. Stylus was removed, and the injector cannula (connected to a 0.5-μL Hamilton syringe [Hamilton, Reno, NV]) was gently inserted into the ipsilateral guide cannula.…”
Section: Melatonin Infusion In the Pfhmentioning
confidence: 99%
“…However, whether ChAT-IR reductions are responsible for the fragmentation of sleep found in adolescent ethanol exposed rats is currently unknown. A reasonable hypothesis is that adolescent alcohol exposure influences multiple sleep systems, as has been reported in adult animals exposed to ethanol (see (Ehlers et al 2013a;Ehlers et al 2013b;Sanchez-Alavez et al 2018;Sharma et al 2010;Sharma et al 2017;Thakkar et al 2010)).…”
Section: Discussionmentioning
confidence: 92%